Author Correction: Differential expression pattern of co-inhibitory molecules on CD4+ T cells in uncomplicated versus complicated malaria. Issue 1 (December 2018) - Abel, Annemieke; Steeg, Christiane; Aminkiah, Francis; Addai-Mensah, Otchere; Addo, Marylyn; Gagliani, Nicola; Casar, Christian; Yar, Denis; Owusu-Dabo, Ellis; Jacobs, Thomas; Mackroth, Maria
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.